2016
DOI: 10.3171/2016.5.jns152809
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy for atypical meningiomas

Abstract: OBJECTIVE The aim of this paper was to evaluate outcomes in patients with atypical meningiomas (AMs) treated with surgery alone compared with surgery and radiotherapy at initial diagnosis, or at the time of first recurrence. METHODS Patients with pathologically confirmed AMs treated at the University of Utah from 1991 to 2014 were retrospectively reviewed. Local control (LC), overall survival (OS), Karnofsky Performance Status (KPS), and toxicity were assessed. Outcomes for patients receiving adjuvant radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 25 publications
(36 reference statements)
2
46
0
Order By: Relevance
“…A recent retrospective review showed a significant improvement in local control for patients receiving early adjuvant radiotherapy, irrespective of EOR. They found time to local failure to be 180 months after surgery and radiotherapy, compared to 46 months for surgery alone (p = 0.002) [7]. Our data confirm these findings, but only with the modality of EBRT, with a cumulative incidence of local failure of only 20.0% for those receiving early EBRT versus 51.4% for surgery alone (p = 0.02).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A recent retrospective review showed a significant improvement in local control for patients receiving early adjuvant radiotherapy, irrespective of EOR. They found time to local failure to be 180 months after surgery and radiotherapy, compared to 46 months for surgery alone (p = 0.002) [7]. Our data confirm these findings, but only with the modality of EBRT, with a cumulative incidence of local failure of only 20.0% for those receiving early EBRT versus 51.4% for surgery alone (p = 0.02).…”
Section: Discussionsupporting
confidence: 82%
“…Managing these patients requires evaluating the role of adjuvant therapy in both patients receiving GTR and STR. A growing body of literature suggests that early adjuvant radiotherapy improves local control [79]; however, the effect on OS is more disputed with some recent studies finding no benefit [7,27]. Some of the inconsistencies reported in the literature could be a result of the variability in the administration of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies 17] and SBMs [18,19] after initial surgical resection. Various forms of adjuvant radiotherapy, including fractionated radiotherapy and stereotactic radiosurgery, have been found to improve local control [16,17,19]. However, the efficacy of adjuvant radiotherapy for the recurrent stage of SBMs remains unclear [16,17].…”
Section: Introductionmentioning
confidence: 99%